A Surprising Choice, an Unusual Path: Natalia Aszkenazy, Poland's First Female Diplomat. - Landa, Ronald D. (Polish Review, 2026)
Natalia Aszkenazy, appointed in October 1941 as attaché in the Soviet Union, took an unusual route to diplomatic service. She had never held a paying job and received no formal training. After coming to the United States as a twenty-five-year-old tourist just before the outbreak of World War II, she served as a volunteer for the Red Cross in New York and later as an honorary member of the Polish Embassy's press and public relations section under career diplomat Jan Drohojowski, whom she eventually married. Her contacts with Polish-American individuals and organizations were expected to facilitate the flow of relief to an estimated 1.5 million Polish refugees scattered throughout the Soviet Union. By the time she arrived in March 1942 at Kuibyshev, the relocated seat of government, a relief program was well underway. She worked first as Ambassador Stanisław Kot's secretary, then in the welfare section, and finally as press attaché before the Soviet Union severed diplomatic relations in April 1943. She returned to the United States to conduct a five-month lecture tour in early 1944. Her appointment made Poland the seventh nation to admit women into diplomatic service. And she helped pioneer the role of diplomat/propagandist, a relatively new element in the conduct of foreign relations that after the war came to be called public diplomacy.